Rebuilding Private Hospital According to Indonesian Health Law Politics - Buamona, Has rul (Veteran Law Review, 2021)
In Article 21 of Law Number 44 of 2009 concerning Hospitals, only private hospitals in the form of PT, do not regulate and even strengthen the position of private hospitals, foundations and associations as a forum for health services in accordance with Pancasila and Article 34 paragraph (3) of the Constitution. 1945 as the legal politics of health services in Indonesia. Therefore, this is the reason for the author to conduct a study with the aim of rebuilding a private hospital in accordance with the character of the Indonesian state which has a social-human spirit. This study focuses on the main problem, namely How should the legal politics of regulating the form of private hospitals in the future. The research method used is normative law or doctrinal methods that are qualitative in nature to analyze data based on norms in laws and regulations that are guided by the precepts of Pancasila as the basis of Indonesian legal politics. The results of this study conclude that in the future the legal entity of a private hospital should not be in the form of a PT, but must be in the form of foundations and associations, because foundations and associations have separate assets and are intended to achieve certain goals in the social and religious fields. The participation of foundations and associations is in accordance with Article 28C paragraph (2) of the 1945 Constitution, which stipulates that "everyone has the right to advance himself in fighting for his rights collectively to build his community, nation and state. Finally, private hospitals, foundations and associations are in accordance with Pancasila and Article 34 paragraph (3) of the 1945 Constitution as the legal political basis for health services.